EFISIENSI TEKNIS DAN EKONOMI PERIKANAN TUNA HAND LINE DI NEGERI TIAL KABUPATEN MALUKU TENGAH - Siahainenia, Priscyllia Franetha; Bawole, Dionisius; Talakua, Willem (Program Studi Agrobisnis Perikanan, Universitas Pattimura, 2019)
The resources of large pelagic including tuna (Thunnus sp) in Maluku are quite potential with moderate status and must be utilized optimally. In Tial, the utilizing of these resources uses hand lines; especially fishing line. Tuna hand line is classified as small-scale fisheries which has various problems. One of it is fishing inputs allocation that leads to inefficient. This study in general aims to analyze the hand line tuna fisheries business based on technical and economical efficiency. It was conducted by using survey method in Tial, Central Maluku Regency for 20 units hand line fishermen. Data was analized by Cobb-Douglas production function approach to identify efficient inputs; several financial parameters to determine business feasibility; and CPUE to measure the level of technical productivity. The results show that efficient production factors are fishermen?s fishing experience and fishing frequency. During the four months of observation, all business units made an average profit of Rp 31,199,139 or Rp 458,810.86/trip. R/C and PP parameters show that the business is feasible to be developed; while the largest ROI (135.2%) is in the 18th business unit. Business units that have CPUE >1 are unit 1st, 2nd, 3rd, 5th, 6th, 9th, 11th, 12th, 13th, 14th, 15th, 16th, 17th, 18th, 19th and 20th. Based on several technical-economical measurements, the hand line tuna fishery business in Tial is efficient and feasible to be developed